Implementation of Regulation of the Director General of Islamic Bimas Number 379/2018 concerning Marriage Guidance as an Effort to Create the Sakinah Family - Mansur, Mansur; Sudirman L, Sudirman L (Al-Iftah: Journal of Islamic studies and society, 2020)
This study discusses aboutimplementation of the regulation of the Director General of Islamic Community Guidance No. 379/2018 regarding marriage guidance as an effort to create a sakinah family.. This study aims to determineimplementation of the regulation of the Director General of Islamic Community Guidance No. 373/2017 regarding marriage guidance as an effort to create a sakinah family.Types of researchisdescriptive qualitative. Descriptive research, location inWatangpulu District, Sidrap Regency mthrough observation, interviews, and documentation studies. Sources of data are the Head of KUA, Penghulu and religious instructors as well as prospective brides.The results of this study indicate that 1) household dynamics in forming a sakinah family in Watangpulu District, Sidrap Regency, family dynamics if not handled seriously will lead to divorce, so that is the basis for the link between marriage and divorce; 2) Supporting factors a) For participants who follow marriage guidance are very enthusiastic. b) Guidance material that is easy to understand, and 3) Implementation of the regulation of the Director General of Islamic Community Guidance No. 379/2018regarding marriage guidance for prospective brides in its implementation is quite effective.